Understanding The Doctrine Of The Trinity - Frederich Oscar Lontoh (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
Many people have difficulty understanding the Trinity. Likewise, many Christians themselves do not understand this basic doctrine. Even more so for people outside of Christianity, they assume that Christians believe in three Gods or even think that God has a sexual relationship with Mary. There is also the opinion that the triune God is one person with three functions. The three views above are not true. Thophilus of Anthiokia was the first to use the term Trinity or trias in Greek. Whereas Tertullian was the first to use this term in Latin form. It was from Tertullian that the terms substance (substance) and person(personal, person) were used in formulating the concept of the Trinity. Every Christian must understand what is fundamental to his faith. The Trinity is a basic doctrine that must be correctly understood and accepted by every Christian. Without a proper understanding of this doctrine, it will undermine other related doctrines, namely the doctrine of creation, the doctrine of Christology, the doctrine of redemption, and the doctrine of eternal life. The trinity doctrine is a doctrine which is accepted by all Christian churches for almost 2000 years. Only heretical schools and deviant movements do not accept this doctrine.